ANALISA PENGURUSAN PROSES KLAIM ASURANSI KECELAKAAN KAPAL YANG MENABRAK BREAKWATER, STUDI KASUS BG. MARITIME LADY DI TELUK PENYU CILACAP - Winarno Winarno; Wim Benhard Manurung (Dinamika Bahari, 2019)
ABSTRACTThe shipping business feels the importance of the risk of financial responsibility arisingfrom the operation of ships, the obligation of ship owners/operators must be responsible forthe safety of passengers and the cargo they carry in the event of an accident causing injuryor causing loss to passengers, as well as loss/damage to transported cargo and losses tothird parties, namely by transferring risk to other parties where the other party as therecipient of the risk and being able to manage the risk are insurance companies. In this casethe ship owner and operator can guarantee the risks of responsibility that arise with P & IClub insurance. In this case the researcher uses a qualitative descriptive writing method todescribe and describe the object under research. In addition, this research also usesobservation, interviews and literature.From an analysis of the matter he added group of researchers from came to theconclusion that the process of and settlement of the insurance claim had been completed andwas although there have been a obstacles faced. Constraints faced in the process andsettlement of claims are complete claims documents, selection of contracting companies, andsocio-economic conditions and weather. The efforts made in reducing the are, research theownership documents contractor in accordance the classification of PT. Pertamina as wellas persuasive approach it cooperates with BMKG case and supervision from PT. Pertaminadivision marine in repairing process